INTANGIBLE CULTURAL HERITAGE: CONCEPTUAL DILEMMAS BETWEEN THE IMMATERIAL AND THE CULTURAL - Khaled Benfafa (International Journal of Innovative Technologies in Social Science, 2025)
Intangible Cultural Heritage is a fundamental pillar of collective identity, encompassing traditions, oral expressions, performing arts, and traditional craftsmanship transmitted across generations. However, its dual nature—both "intangible" and "cultural"—poses significant conceptual and policy challenges, making This paper explores the interplay between the symbolic dimension of ICH and its role in shaping collective identity while examining the impact of globalization and digitalization on its transmission and sustainability. It also analyzes international and local strategies for its preservation, highlighting the challenges faced by developing countries in documenting and protecting ICH within evolving cultural contexts. By offering a comprehensive perspective on contemporary approaches to ICH conservation, this study aims to propose innovative mechanisms to ensure its continuity amid rapid social and cultural transformations.